The utility of the ultrasonographic assessment of the lower leg muscles to evaluate sarcopenia and muscle quality in older adults. Issue 2 (23rd December 2020) - Isaka, Masaaki; Sugimoto, Ken; Fujimoto, Taku; Yasunobe, Yukiko; Xie, Keyu; Onishi, Yuri; Yoshida, Shino; Takahashi, Toshimasa; Kurinami, Hitomi; Akasaka, Hiroshi; Takeya, Yasushi; Yamamoto, Koichi; et al.
Abstract: Background: The assessment of muscle quality is expected to help predict the prognosis of sarcopenia and examine the response to intervention. Ultrasonography can be used to evaluate approaches for determining muscle quantity and quality. We focused on the lower leg muscles and examined the relationship between the ultrasonographic assessments and the components of sarcopenia and muscle quality by comparing them with those of the quadriceps muscle (QFM). Methods: 47 physically healthy older participants aged 78.3 ± 6.0 years (53% male) were enrolled in this cross‐sectional study. Muscle thickness (MT) and echo intensity (EI) of the lower leg muscles and QFM were assessed with ultrasonography. Muscle mass, grip strength, and gait speed, and lower leg muscle strength were measured. Muscle quality was calculated using a formula: leg muscle strength/leg muscle mass. Results: The MTs and EIs of the tibialis anterior muscle (TA) and QFM were significantly associated with grip and leg strength. We observed a significant correlation in the MTs and EIs of the lower leg muscles and QFM. The EIs of the lower leg muscles and QFM showed significant negative correlations with muscle quality. In the multiple linear regression model, the EI of the TA and QFM was extracted as an independent factor of muscle quality (TA: β = −0.35, p = 0.0358; QFM: β = −0.30, p = 0.0327). Conclusions: The ultrasonographic assessments of the lower leg muscles, especially the TA, were associated with sarcopenia components and muscle quality equal to or greater than those of the QFM.